Internalisasi Nilai Pendidikan Agama Islam Pada Kegiatan Ekstakurikuler Rohaniah Islam SMA IT Ar-Rohmma Kretek Bantul Yogyakarta - Muhammad Adnan Firdaus; Ruslan Rasid; Musdalifah Musdalifah; Achmad Budi Susetyo; Hardining Estu Murdinar; M. Zidny Nafi’ Hasbi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
Internalization of Islamic religious values is a process of putting religious values fully into the heart so Internalization of Islamic religious values is a process of putting religious values fully into the heart so that the spirit and soul move based on the teachings of Islam. The purpose of the research was to describe the implementation of internalization of Islamic religious values through extracurricular activities of Islamic spirituality at SMA IT Ar-Rohmah Kretek Bantul Yogyakarta. This study uses qualitative research. The results of this study show that the process of internalizing Islamic religious values through extracurricular activities of Islamic spirituality uses two ways, namely direct and indirect. The supporting factor is that most of the students come from religious families and educated families and the availability of infrastructure facilities